2018
DOI: 10.1016/j.ijscr.2018.02.033
|View full text |Cite
|
Sign up to set email alerts
|

A case report on the successful perioperative management of hepatectomy for hepatocellular carcinoma in a patient with von Willebrand disease

Abstract: HighlightsAlthough von Willebrand disease (VWD) is a common inherited bleeding disease, only 1 case of hepatectomy in a patient with VWD has been described.Perioperative hemostatic management is important especially in patients with VWD undergoing surgery because of the dysfunction of the platelet and destabilization of the blood clotting factor VIII.The patient was successfully treated by administering factor VIII/von Willebrand factor concentrate and by measuring activated partial thromboplastin time as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the extremely low platelet count in the present case was considered to have been caused by type 2B VWD, which often coexists with thrombocytopenia [ 4 ]. Since the protocol of VWF/factor VIII administration in the present case was similar to that in previous reports [ 7 , 12 , 13 ], the extremely low preoperative platelet counts in the present patient might have caused the severe bleeding tendency.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Therefore, the extremely low platelet count in the present case was considered to have been caused by type 2B VWD, which often coexists with thrombocytopenia [ 4 ]. Since the protocol of VWF/factor VIII administration in the present case was similar to that in previous reports [ 7 , 12 , 13 ], the extremely low preoperative platelet counts in the present patient might have caused the severe bleeding tendency.…”
Section: Discussionsupporting
confidence: 80%
“…Since the protocol of VWF/factor VIII administration in the present case was similar to that in previous reports [ 7 , 12 , 13 ], the extremely low preoperative platelet counts in the present patient might have caused the severe bleeding tendency.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…15 Other case reports and studies have reported reassuring outcomes using an organized approach to determine and administer prophylactic therapies for patients with vWD undergoing surgery. 1619 Thus, we recommend the following when preparing for endoscopy for a patient with vWD. First, evaluate the subtype of vWD.…”
Section: Discussionmentioning
confidence: 99%